1998
DOI: 10.1007/s004290050168
|View full text |Cite
|
Sign up to set email alerts
|

Ultracytochemistry of 3β-hydroxysteroid dehydrogenase in Leydig cell precursors and vascular endothelial cells of the postnatal rat testis

Abstract: In the biosynthesis of steroid hormones 3beta-hydroxysteroid dehydrogenase (3beta-HSD) is a key enzyme. The present report describes the subcellular localization of the enzyme in the fetal-type Leydig cells, the fibroblast-like precursors of adult-type Leydig cells and in endothelial cells of interstitial capillaries. Histochemical methods for light microscopy and ultracytochemical methods for electron microscopy were used on rat testes of postnatal day 15. 3beta-HSD reactivity was located at subcellular level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
3
20
1
Order By: Relevance
“…All cells expressing CYP11A1 during the initial phases of differentiation (around 8 days) were peritubular. From this evidence we cannot rule out a perivascular origin for Leydig cells, and there are other studies suggesting a minor contribution from this source (Haider et al 1995, Haider & Servos 1998), but it is unlikely to be the major site of Leydig cell precursor differentiation.…”
Section: Discussionmentioning
confidence: 70%
“…All cells expressing CYP11A1 during the initial phases of differentiation (around 8 days) were peritubular. From this evidence we cannot rule out a perivascular origin for Leydig cells, and there are other studies suggesting a minor contribution from this source (Haider et al 1995, Haider & Servos 1998), but it is unlikely to be the major site of Leydig cell precursor differentiation.…”
Section: Discussionmentioning
confidence: 70%
“…In our studies all cells expressing CYP11A1 were in the peritubular region and we saw no evidence of perivascular development of Leydig cells . We cannot rule out a perivascular origin for Leydig cells from this evidence, and there are other studies suggesting a minor contribution from this source (Haider et al, 1995;Haider and Servos, 1998), but it is unlikely to be the major site of Leydig cell precursor differentiation.…”
Section: Adult Leydig Cellsmentioning
confidence: 66%
“…Surprisingly, the immediate progenitors of the adult Leydig cells also remain in some doubt. Earlier studies indicated that the adult Leydig cells differentiate from peritubular mesenchymal cells (Haider et al, 1995;Haider and Servos, 1998;Russell et al, 1995;Ariyaratne et al, 2000). A more recent study has reported, however, that Leydig cells develop from perivascular smooth muscle cells and pericytes during normal development or during Leydig cell regeneration following ablation with the cytotoxic drug ethane dimethane sulphonate (EDS) (Davidoff et al, 2004).…”
Section: Adult Leydig Cellsmentioning
confidence: 99%
“…Immunocytochemical localization of 17 -HSD was noted in blood vessel walls of human prostate also (El-Alfy et al 1999). Haider & Servos (1998) showed for first time the presence of 3 -HSD in the endothelial cells of the rat testis capillaries; El-Alfy et al (1999) demonstrated the presence 3 -HSD by immunocytochemistry in blood vessel walls of the human prostate. The function of the steroidogenic intracrine enzymes in the blood vessels is unknown.…”
Section: Discussionmentioning
confidence: 86%
“…The presence of 3 -HSD in pituitary endothelial cells is an intriguing finding because, to our knowledge, steroidogenic activity in pituitary blood vessels has not previously been demonstrated. Earlier studies have reported the expression of steroidogenic intracrine enzymes in the vascular structure of various other organs (Haider & Servos 1998, Pelletier et al 1998, El-Alfy et al 1999, Harada et al 1999. Pelletier et al (1998) described the presence of two different subtypes of 5 -reductase mRNA in the blood vessel wall of human prostate and skin.…”
Section: Discussionmentioning
confidence: 99%